Neuro-mechanical determinants of repeated treadmill sprints - Usefulness of an “hypoxic to normoxic recovery” approach - GIRARD, Olivier; Brocherie, Franck; Morin, Jean-Benoit; Millet, Gregoire P. (Frontiers in Physiology, 2015)
To improve our understanding of the limiting factors during repeated sprinting, we manipulated hypoxia severity during an initial set and examined the effects on performance and associated neuro-mechanical alterations during a subsequent set performed in normoxia. On separate days, thirteen active males performed eight 5-s sprints (recovery = 25 s) on an instrumented treadmill in either normoxia near sea-level (SL; FiO2 = 20.9%), moderate (MH; FiO2 = 16.8%) or severe normobaric hypoxia (SH; FiO2 = 13.3%) followed, 6 min later, by four 5-s sprints (recovery = 25 s) in normoxia. Throughout the first set, along with distance covered [larger sprint decrement score in SH (-8.2%) compared to SL (-5.3%) and MH (-7.2%); P<0.05)], changes in contact time, step frequency and root mean square activity (surface electromyography) of the quadriceps (rectus femoris muscle) in SH exceeded those in SL and MH (P<0.05). During first sprint of the subsequent normoxic set, the distance covered (99.6%, 96.4% and 98.3% of sprint 1 in SL, MH and SH, respectively), the main kinetic (mean, horizontal and resultant forces) and kinematic (contact time and step frequency) variables as well as surface electromyogram of quadriceps and plantar flexor muscles were fully recovered, with no significant difference between conditions. Despite differing hypoxic severity levels during sprints 1 to 8, performance and neuro-mechanical patterns did not differ during the four sprints of the second set performed in normoxia. In summary, under the circumstances of this study (participant background, exercise-to-rest ratio, hypoxia exposure), sprint mechanical performance and neural alterations were largerly influenced by the hypoxia severity in an initial set of repeated sprints. However, hypoxia had no residual effect during a subsequent set performed in normoxia. Hence, the recovery of performance and associated neuro-mechanical alterations was complete after resting for 6 min near sea level, with a similar fatigue pattern across conditions during subsequent repeated sprints in normoxia.